Acute arterial baroreflex‐mediated changes in plasma catecholamine concentrations in a chronic rat model of myocardial infarction. Issue 15 (5th August 2016) - Kawada, Toru; Akiyama, Tsuyoshi; Li, Meihua; Zheng, Can; Turner, Michael J.; Shirai, Mikiyasu; Sugimachi, Masaru
Abstract: While it may be predictable that plasma norepinephrine (NE) concentration changes with efferent sympathetic nerve activity (SNA) in response to baroreceptor pressure inputs, an exact relationship between SNA and plasma NE concentration remains to be quantified in heart failure. We examined acute baroreflex‐mediated changes in plasma NE and epinephrine (Epi) concentrations in normal control (NC) rats and rats with myocardial infarction (MI) ( n  = 6 each). Plasma NE concentration correlated linearly with SNA in the NC group (slope: 2.17 ± 0.26 pg mL −1  % −1, intercept: 20.0 ± 18.2 pg mL −1 ) and also in the MI group (slope: 19.20 ± 6.45 pg mL −1  % −1, intercept: −239.6 ± 200.0 pg mL −1 ). The slope was approximately nine times higher in the MI than in the NC group ( P  < 0.01). Plasma Epi concentration positively correlated with SNA in the NC group (slope: 1.65 ± 0.79 pg mL −1  % −1, intercept: 115.0 ± 69.5 pg mL −1 ) and also in the MI group (slope: 7.74 ± 2.20 pg mL −1  % −1, intercept: 24.7 ± 120.1 pg mL −1 ). The slope was approximately 4.5 times higher in the MI than in the NC group ( P  <   0.05). Intravenous administration of desipramine (1 mg kg −1 ) significantly increased plasma NE concentration but decreased plasma Epi concentration in both groups, suggesting that neuronal NE uptake had contributed to the reduction in plasma NE concentration. These results indicate that high levels of plasma catecholamine in MI rats were still under the influence of baroreflex‐mediated changes in SNA, and may provide additional rationale for applying baroreflex activation therapy in patients with chronic heart failure. Abstract : Plasma catecholamine concentrations are significantly elevated in a chronic rat model of myocardial infarction. However, the catecholamine levels are still under the influence of carotid sinus baroreflex‐mediated changes in sympathetic nerve activity, which may provide additional rationale for sympathetic suppression via the baroreflex activation therapy in patients with chronic heart failure.